Algebraische Zahlentheorie: 5.8. bis 11.8.1984 - Jehne, Wolfram; Leopoldt, Heinrich-Wolfgang; Roquette, Peter (Tagungsbericht, 1984)
J. Antoniadis Thessaloniki; W. Bauer, Regensburg; H. Benz, Köln; D. Bernardi, Paris; J. Brinkhuis, Rotterdam; J. Chahal, Provo; H. Cohn, New York; C. Deninger, Regensburg; V. Diekert, Hamburg; M. Eichler, Arlesheim; G. Everest, Norwich; G. Frei-Imfeld, Quebec; A. Fröhlich, Wimbeldon; W.-D. Geyer, Erlangen; G. Gras, Besancon; K. Gyory, Debrecen; F. Halter-Koch, Graz; D. Haran, Erlangen; H. Jacobinsk, Göteborg; M. Jaden, Tel Aviv; W. Jehne, Köln; C. U. Jensen, Copenhagen; E. Kleinert, Köln; N. Klingen, Köln; E. Lamprecht, Saarbrücken; J. B. Leicht, Heidelberg; H. W. Leopoldt, Karlsruhe; A. Leutbecher, München; F. Lorenz, Münster; G. Martens, Erlangen; B. H. Matzat, Karlsruhe; T. Metsänkylä, Turku; W. Narkiewicz, Wroclaw; J. Neukirch, Regensburg; Nguyen Quang Do, Paris; H. Opolka, Münster; R. Perlins, Baton Rouge; A. Prestel, Konstanz; H. P. Rehm, Karlsruhe; J. Ritter, Augsburg; P. Roquette, Heidelberg; R. Schertz, Augsburg; A. Schinzel, Warszawa; C. Schmidt, Bures-sur-Yvette; P. Schneider, Heidelberg; L. Skula, Brno; J. Sonn, Haifa; M. Taylor, Cambridge UK; N. Walter, Mannheim; K. Wingberg, Regensburg; H. G. Zimmer, Saarbrücken